Suppression of LINC00707 alleviates lipopolysaccharide-induced inflammation and apoptosis in PC-12 cells by regulated miR-30a-5p/Neurod 1. Issue 11 (2nd November 2019) - Zhu, Shiping; Zhou, Zhigang; Li, Zhizhong; Shao, Jianli; Jiao, Genlong; Huang, Yu′En; Lin, Yongxin
ABSTRACT: Long noncoding RNA (lncRNA) has emerged as a pivotal regulator improving neural regeneration in the progression of spinal cord injury (SCI). However, whether lncRNAs can be targeted for therapeutic intervention of SCI remains unclear. In this study, we found that LINC00707 expression was significantly up-regulated in lipopolysaccharide (LPS)-treated PC-12, a model that mimics nerve cell injury in an inflammatory environment after SCI. Suppression of LINC00707 alleviated LPS-induced inflammation and apoptosis in PC-12 cells. Furthermore, we found that LINC00707 adsorbed miR-30a-5p and silenced miR-30a-5p or overexpressed Neurod 1 reversed the effect of LINC00707 on the inflammation and apoptosis of LPS-treated PC-12 cells. These findings revealed that LINC00707 alleviates LPS-induced inflammation and apoptosis in PC-12 cells by targeting miR-30a-5p/Neurod 1, providing a preliminary theoretical basis for the clinical application of LINC00707 in SCI. Graphical abstract: : Suppression of LINC00707 alleviates lipopolysaccharide-induced inflammation and apoptosis in PC-12 cells by regulated miR-30a-5p/Neurod 1.